The Rice AAA-ATPase OsFIGNL1 Is Essential for Male Meiosis - Zhang, Peipei; Zhang, Yingxin; Sun, Lianping; Sinumporn, Sittipun; Yang, Zhengfu; Sun, Bin; Xuan, Dandan; Li, Zihe; Yu, Ping; Wu, Weixun; Wang, Kejian; Cao, Liyong; et al. (Frontiers in Plant Science, 2017)
Meiosis is crucial in reproduction of plants and ensuring genetic diversity. Although several genes involved in homologous recombination and DNA repair have been reported, their function in rice (Oryza sativa) male meiosis remains poorly understood. Here, we isolated and characterized the rice OsFIGNL1 (OsFidgetin-like 1) gene, encoding a conserved AAA-ATPase, and explored its function and importance in male meiosis and pollen formation. The rice Osfignl1 mutant exhibited normal vegetative growth, but failed to produce seeds and displayed pollen abortion phenotype. Phenotypic comparisons between the wild type and Osfignl1 mutant demonstrated that OsFIGNL1 is required for anther development, and that the recessive mutation of this gene causes male sterility in rice. Complementation and CRISPR/Cas9 experiments demonstrated that wild-type OsFIGNL1 is responsible for the male sterility phenotype. Subcellular localization showed that OsFIGNL1-green fluorescent protein was exclusively localized in the nucleus of rice protoplasts. Male meiosis in the Osfignl1 mutant exhibited abnormal chromosome behavior, including chromosome bridges and multivalent chromosomes at diakinesis, lagging chromosomes, and chromosome fragments during meiosis. Yeast two-hybrid assays demonstrated OsFIGNL1 could interact with RAD51A1, RAD51A2, DMC1A, DMC1B and these physical interactions were further confirmed by BiFC assay. Taken together, our results suggest that OsFIGNL1 plays an important role in regulation of male meiosis and anther development.